1997
DOI: 10.1177/095624789700900115
|View full text |Cite
|
Sign up to set email alerts
|

Urban equity and urban health: using existing data to understand inequalities in health and environment in Accra, Ghana and São Paulo, Brazil

Abstract: SUMMARY:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 2 publications
1
26
0
Order By: Relevance
“…For example, in 1990 in Monterey, Mexico, 48% of households situated in the lowest income district of the city had one bedroom in comparison to 16% of households in the most affluent district (48). Similar trends have been uncovered in major urban areas in other developing countries (125).…”
Section: Residential Crowdingmentioning
confidence: 64%
“…For example, in 1990 in Monterey, Mexico, 48% of households situated in the lowest income district of the city had one bedroom in comparison to 16% of households in the most affluent district (48). Similar trends have been uncovered in major urban areas in other developing countries (125).…”
Section: Residential Crowdingmentioning
confidence: 64%
“…7,14,15 More than an ecological epidemiological study of intra-urban differences, it practiced the exercise in negotiation of constructing composite indicators, b,c which influenced a set of research into violence, quality of life and social exclusion/inclusion. [4][5][6] One of those pieces of research was the Violence Risk Map of Sao Paulo, SP, Southeastern Brazil.…”
Section: A Possible Starting Pointmentioning
confidence: 99%
“…Moreover, when the cities were divided into zones, according to socio-economic status (SES) indicators, age-adjusted rates of mortality from heart disease were 2.3 times higher for the population in the lowest SES zone compared to rates of the highest SES zone. Considerable differences in mortality rates due to respiratory problems were also found [5,6]. Additionally, studies have shown that child morbidity and mortality rates in poor urban communities can equal or surpass those in rural communities [7,8].…”
Section: Introductionmentioning
confidence: 99%